Mao's Forgotten Successor - Weatherley, Robert. author. aut Link
XII, 203 p.
Keywords: Hua Guofeng succeeded Mao in 1976, emerging almost out of nowhere following an unexceptional career in Shanxi and Hunan. In just over two years, Hua had been eclipsed by Deng Xiaoping, a more politically shrewd, progressive and charismatic figure. If Hua's rise to power was remarkable, then this fall was even more so.